Improvement of radiotherapy with an ozone-carried liposome nano-system for synergizing cancer immune checkpoint blockade. (December 2022) - Zheng, Dan; Li, Yanchu; Song, Linlin; Xu, Tianyue; Jiang, Xian; Yin, Xiaomeng; He, Yinbo; Xu, Jinshun; Ma, Xuelei; Chai, Li; Xu, Jie; Hu, Jianping; et al.
Abstract: Radiotherapy is a compatible regimen for synergizing immune checkpoint blockade therapy by promoting immunogenic cell death. To improve the efficiency of irradiation-induced neoantigen generation, we designed and developed an ozone-carrying liposome perfluorodecalin (PFD) nano-system (O3 _PFD@Liposome) which promoted ozone solubility by 18.4-fold compared to that in water solution. The O3 _PFD@Liposome particle remarkably improved the irradiation-induced hydroxyl radical generation. Evaluation of sub-cellular biodistribution indicated that the nano-system could be efficiently internalized by tumor cells. Upon released inside tumor cells, ozone generated reactive oxygen species under the stimulation of X-ray irradiation. Notably, O3 _PFD@Liposome significantly prompted anti-tumor efficacy of radiotherapy without inducing severe adverse effects. The combo regimen with radiotherapy and ozone potently enhanced the infiltration of lymphocytes in the tumor microenvironment by inducing immunogenic cell death, releasing neoantigens, and relieving hypoxia symptom. Consequently, the combination of ozone-fueled irradiation and PD-1 blockade synergistically inhibited the growth of primary and abscopal tumors. Graphical Abstract: ga1 Highlights: Ozone may serve as an efficient donor of ROS and oxygen under the agitation of irradiation. Ozone-loaded perfluorodecalin liposome sensitizes radiotherapy by enhancing ROS productivity and attenuating hypoxia. Combination of O3 _PFD@Liposome and irradiation promotes tumor-infiltrating lymphocyte by augmenting immunogenic cell death. On top of ozone-fueled irradiation, PD-1 blockade further enhances growth inhibition of primary and abscopal tumors.